Economic implications of ddPCR and NGS-based noninvasive prenatal testing for fetal aneuploidy screening - Mittal, Amit Kumar; Shekhawat, Dolat Singh; Patel, Mamta; Singh, Pratibha; Singh, Kuldeep (Intelektual Pustaka Media Utama, 2024)
Noninvasive prenatal testing (NIPT) heralds a transformative era in prenatal care, revolutionizing fetal health assessment. The recent adoption of aneuploidy screening signifies a significant advancement in prenatal genetic care in India. The current study aimed to assess the cost-effectiveness of ddPCR-based NIPT for detecting chromosome aneuploidies, comparing it with the next-generation sequencing (NGS) platform. This study adopts a laboratory-based observational approach to investigate the cost implications of NIPT for trisomies 13, 18, and 21 using ddPCR and NGS technologies. A meticulously designed cost analysis methodology was employed, adhering to established standards. The yearly capital and operational costs of NIPT were calculated with precision, focusing on the specific methods associated with ddPCR and NGS. The calculated annual capital and operating costs for NIPT using the ddPCR were 16,411 and 246,540 while those using the NGS platform were 91,440 and 250,560, respectively. The total cost of NIPT using ddPCR for 2,400 tests was 262,951, with an estimated cost per test of 110. In contrast, the total cost of NIPT using the NGS platform for 600 tests was 342,000, resulting in an estimated cost per test of 570. The ddPCR is five times more cost-effective. Moreover, it exhibits a fourfold reduction in time expenditure, attributable to streamlined procedures and does not require a complex bioinformatics analysis compared to the NGS. Moreover, this preliminary outcome on cost analysis for NIPT using ddPCR, as opposed to the NGS platform, can be extended to the health technology assessment (HTA) perspective for prenatal screening programs.